Structural Information and Communication Complexity : 22nd International Colloquium, SIROCCO 2015, Montserrat, Spain, July 14-16, 2015. Post-Proceedings - Scheideler, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 22nd International Colloquium on Structural Information and Communication Complexity, SIROCCO 2015, held in Montserrat, Spain, in July 2015. The 30 full papers presented together with 2 invited papers were carefully reviewed and selected from 78 submissions. The papers focus on the study of the interplay between communication and knowledge in multi-processor systems from both the qualitative and quantitative viewpoints.
Communication Patterns and Input Patterns in Distributed Computing -- Clock Synchronization and Estimation in Highly Dynamic Networks: An Information Theoretic Approach -- Node Labels in Local Decision -- Exact bounds for distributed graph colouring -- Essential Traffic Parameters for Shared Memory Switch Performance. -Scheduling Multipacket Frames With Frame Deadlines -- A Randomized Algorithm for Online Scheduling -- Online Admission Control and Embedding of Service Chains -- Optimizing Spread of Inuence in Social Networks via Partial Incentives -- Approximation Algorithms For Multi-Budgeted Network Design Problems -- Simple Distributed + 1 Coloring in the SINR Model -- Nearly Optimal Local Broadcasting in the SINR Model with Feedback -- Byzantine Gathering in Networks -- Signature-free Asynchronous Byzantine Systems: From Multivalued to Binary Consensus -- A Fast Network-Decomposition Algorithm and its Applications to Constant-Time Distributed Computation -- Path-Fault-Tolerant Approximate Shortest-Path Trees -- A faster computation of all the best swap edges of a tree spanner -- Randomized OBDD-Based Graph Algorithms -- On Fast and Robust Information Spreading in the Vertex-Congest Model -- Under the Hood of the Bakery Algorithm: Mutual Exclusion as a Matter of Priority -- The Computability of Relaxed Data Structures: Queues and Stacks as Examples -- Comparison-based Interactive Collaborative Filtering -- Coalescing walks on rotor-router systems.
Keywords: Computer software; Computer Communication Networks; Computational complexity; Data structures (Computer scienc; Algorithms; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Discrete Mathematics in Computer Science; Data Structures; Algorithms